Evolution of Maastrichtian paleoproductivity along the southern Tethys margin (Jordan): From upwelling to runoff - Maria Ardila-Sanchez; Jihede Haj Messaoud; Amir Kalifi; Khalil Ibrahim; Muhammad Usman; Israa S. Abu-Mahfouz; Samer Aljurf; Volker Vahrenkamp; John H. Powell; Frans van Buchem (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Spatial analysis of environmental policy stringency effect on the environmental performance of European countries: mitigation options through green growth and green technological innovation - Maria Shabir; Asif Javed; Snober Fazal; Nimra Usman (Environment, Development and Sustainability, 2026)
Against a backdrop of worsening environmental problems, sustainable development and the conservation and protection of nature have become focal points of current debate. Because burning fossil fuels jeopardizes global sustainability, transitioning to green energy worldwide is recognized as a primary strategy to address climate change. Prior work has concentrated on the temporal dynamics of environmental deterioration. This study, by contrast, examines the drivers of ecological footprint (EFP) from a spatio-temporal perspective, focusing on the extent to which green growth (GG), green technological innovation (GTI), and environmental policies (EPS) influence ecological sustainability across 27 European Union (EU) member states over the 1996 to 2020 period. The results of the Wald and likelihood ratio tests confirm that the spatial autoregressive (SAR) model is most suitable for the analysis. The empirical findings indicate that GG, GTI, and EPS in a given country reduce EFP both domestically and in neighbouring countries. Moreover, we examine regional heterogeneity by splitting the sample into Eastern and Western European groups. The empirical findings of heterogeneity analysis reveal that GG exacerbates EFP in Eastern Europe but mitigates it in Western Europe. Policymakers need to take tangible steps to limit environmental harm, incentivize renewable energy, and diversify energy sources. These findings suggest that cross-border cooperation is essential for the sample economies to promote GG and GTI, implement sustainable growth strategies, and improve production efficiency, thereby supporting better environmental outcomes.

Laboratory and greenhouse endophytic colonization of tomato by three entomopathogenic fungal isolates for the management of Tetranychus urticae and field efficacy trials - Waqas Wakil; Maria C. Boukouvala; Nickolas G. Kavallieratos; Aqsa Naeem; Syed Adnan Haider; Muhammad Usman Ghazanfar; Pasco B. Avery (Crop Protection, 2025)

Field-based evaluation of sugarcane bagasse biochar for managing root-knot nematodes in tomato - Maria Fayyaz; Amjad Abbas; Usman Arshad; Farrukh Azeem; Faiz Ahmad Joyia; Abdelaziz Hajjaji; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Integrating nutrition into environmental impact assessments reveals limited sustainable food options within planetary boundaries - Venla Kyttä; Hafiz Usman Ghani; Tiina Pellinen; Anna Kårlund; Marjukka Kolehmainen; Anne-Maria Pajari; Hanna L. Tuomisto; Merja Saarinen (Sustainable Production and Consumption, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Unlocking the structure-activity relationship of hierarchical MFI zeolites towards the hydrocracking of HDPE - Muhammad Usman Azam; Auguste Fernandes; Maria João Ferreira; Alan J. McCue; Inês Graça; Waheed Afzal (Fuel, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Enhanced lead phytoextraction and soil health restoration through exogenous supply of organic ligands: Geochemical modeling” - Maria Manzoor; Muhammad Shafiq; Iram Gul; Usman Rauf Kamboh; Dong-Xing Guan; Abdulrahman Ali Alazba; Sven Tomforde; Muhammad Arshad (Journal of Environmental Management, 2023)

Environmental cost of natural resources, globalization, and economic policy uncertainty in the G-7 bloc: do human capital and renewable energy matter? - Awais Dastgeer; Maria Shabir; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Analyzing asymmetric ecological performance under structural change, technological innovation, and trade diversification: fresh insights from the USA - Md Minhazul Islam; Paiman Ahmad; Maria Shabir; Muhammad Usman; Mustafa Kamal (Environmental Science and Pollution Research, 2023)

Role of oil shocks in US stock market volatility: A new insight from GARCH-MIDAS perspective - Usman Ghani; Bo Zhu; Maria Ghani; Nasir Khan; Raja Danish Akbar khan (Resources Policy, 2023)

β-Sitosterol could serve as a dual inhibitor of Trypanosoma congolense sialidase and phospholipase A2: in vitro kinetic analyses and molecular dynamic simulations - Suleiman Aminu; Ammar Usman Danazumi; Zainab Aliyu Alhafiz; Maria Wiktoria Gorna; Mohammed Auwal Ibrahim (Molecular Diversity, 2023)

Kidney changes in lambs fed cactus pear varieties resistant to Dactylopius opuntiae as the only roughage - Usman Abdulhadi Usman; Anidene Christina Alves de Moraes; Tomás Guilherme Pereira da Silva; Ângela Maria Vieira Batista; Pierre Castro Soares; Carolina Akiko Sato Cabral de Araújo; Francisco Fernando Ramos de Carvalho; Valdemiro Amaro da Silva Júnior (Tropical Animal Health and Production, 2022)

Trajectory of anti-SARS-COV-2 IgG antibodies from onset of symptoms to 6 months in a cohort of Pakistani patients - Maria Mehmood; Haleema Usman Khan; Muhammad Ihtesham Khan; Ishaq Khan; Rajaa Mohammad Al-Raddadi; Steve Harakeh; Yasar Mehmood Yousafzai (Infectious Diseases, 2022)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

Lead availability and phytoextraction in the rhizosphere of Pelargonium species - Maria Manzoor; Iram Gul; Aamir Manzoor; Usman Rauf Kamboh; Kiran Hina; Jean Kallerhoff; Muhammad Arshad (Environmental Science and Pollution Research, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Field Survey and Numerical Modelling of the December 22, 2018 Anak Krakatau Tsunami - Jose C. Borrero; Tubagus Solihuddin; Hermann M. Fritz; Patrick J. Lynett; Gegar S. Prasetya; Vassilios Skanavis; Semeidi Husrin; Kushendratno; Widjo Kongko; Dinar C. Istiyanto; August Daulat; Dini Purbani; et al. (Pure and Applied Geophysics, 2020)

Analysis of asymmetries in the nexus among clean energy and environmental quality in Pakistan - Ahmed Usman; Sana Ullah; Ilhan Ozturk; Muhammad Zubair Chishti; Syeda Maria Zafar (Environmental Science and Pollution Research, 2020)

Polyoxometalates as potent inhibitors for acetyl and butyrylcholinesterases and as potential drugs for the treatment of Alzheimer’s disease - Jamshed Iqbal; Maria Barsukova-Stuckart; Masooma Ibrahim; Syed Usman Ali; Aftab Ahmed Khan; Ulrich Kortz (Medicinal Chemistry Research, 2013)